2012
DOI: 10.2135/cropsci2011.10.0533
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Elite Maize (Zea mays L.) Germplasm across Maturity Zones

Abstract: Transfer of elite lines across maturity zones is important because it facilitates the exploitation of indirect selection gain. The main goal of this study was to investigate strategies to guide the transfer of elite lines from Southern Europe to the U.S. Corn Belt. Testcrosses of progenies of six biparental populations derived from a diallel cross of four Southern European elite lines were evaluated together with adapted commercial checks in 10 Southern European and six U.S. Corn Belt environments in 2007 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…When multiplying allochthonous varieties, we should expect changes in some adaptation-related traits, such as flowering time or grain moisture (Peña-Asín et al 2013). Steinhoff et al (2012) concluded that it is possible to use some genotypes from southern Europe for breeding in the USA, but the election of genotypes cannot rely on data determined in Southern Europe because gene × genetic background interactions and epistasis effects affect the morphological variability of genotypes. Therefore, there are effects of environmental adaptation on both the phenotypic and the genetic structure when genotypes are used in environments different to their original locations (Revilla et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…When multiplying allochthonous varieties, we should expect changes in some adaptation-related traits, such as flowering time or grain moisture (Peña-Asín et al 2013). Steinhoff et al (2012) concluded that it is possible to use some genotypes from southern Europe for breeding in the USA, but the election of genotypes cannot rely on data determined in Southern Europe because gene × genetic background interactions and epistasis effects affect the morphological variability of genotypes. Therefore, there are effects of environmental adaptation on both the phenotypic and the genetic structure when genotypes are used in environments different to their original locations (Revilla et al 2005).…”
Section: Discussionmentioning
confidence: 99%